2012
DOI: 10.1186/1471-2164-13-s3-s4
|View full text |Cite
|
Sign up to set email alerts
|

A natural language interface plug-in for cooperative query answering in biological databases

Abstract: BackgroundOne of the many unique features of biological databases is that the mere existence of a ground data item is not always a precondition for a query response. It may be argued that from a biologist's standpoint, queries are not always best posed using a structured language. By this we mean that approximate and flexible responses to natural language like queries are well suited for this domain. This is partly due to biologists' tendency to seek simpler interfaces and partly due to the fact that questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The novelty of our system is that such knowledge is derived by the system on its own and no explicit requests need to be made. In a more recent work [32,31], it was shown that an ontology based logical query language ConLog can be used to non-intrusively capture semantic knowledge and query response generated without such explicit knowledge entailed response computation. In this paper, our goal is to show that a canonical representation, as shown in figures 3(a) through 3(f), can be used to compose queries in a logic based language such as Datalog without user intervention.…”
Section: A Motivating Examplementioning
confidence: 99%
See 2 more Smart Citations
“…The novelty of our system is that such knowledge is derived by the system on its own and no explicit requests need to be made. In a more recent work [32,31], it was shown that an ontology based logical query language ConLog can be used to non-intrusively capture semantic knowledge and query response generated without such explicit knowledge entailed response computation. In this paper, our goal is to show that a canonical representation, as shown in figures 3(a) through 3(f), can be used to compose queries in a logic based language such as Datalog without user intervention.…”
Section: A Motivating Examplementioning
confidence: 99%
“…Augmenting structured databases with semantic knowledge for the purpose of knowledge rich queries have been studied in the context of NLQs [32,31], and structured database integration [34]. Despite many such efforts, articulating application description by domain scientists in Biology to facilitate knowledge rich queries remain a significant challenge.…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Cimiano et al (2009) describes different paradigms proposed in the past for querying information collections, among them form filling, query-by-example or menu-based approaches, as well as NLIs, either relying on controlled language or on more or less free language input. Obviously, Natural Language (NL) searching probably constitute the most flexible and effective approach for interrogating a biological DB (Jamil, 2012). Since many biological DBs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…GenBank or UCSC Genome Browser) employ graphical interfaces that are not prepared for arbitrary questioning, previous effort has been made to build NL strategies oriented to Biomedicine and Biotechnology DBs (e.g. Jamil, 2012;Goldsmith et al, 2009;Clegg & Shepherd, 2007;Distelhorst et al, 2003). As Cimiano et al (2009) states, while the querying paradigm based on NL is generally deemed to be the most intuitive from a usage point of view, it has also been shown to be the most difficult to realize effectively.…”
Section: Introductionmentioning
confidence: 99%